Critical Temperature Shift for Stress Induced Voiding in Advanced Cu Interconnects for 32 nm and Beyond. (2016) - Morusupalli, Rao; Rao, R.; Lee, Tae-Kyu; Shen, Yu-Lin; Kunz, M.; Tamura, N.; Budiman, A.S.
Abstract: Work showing evidence of a shift in the Stress Migration (SM) peak profile temperature for smaller interconnect linewidths typically associated with the 32 nm technology node and beyond is presented here. With other parameters (fabrication, materials, line thickness and via diameter being kept nominal among all these samples), this clear shift towards the lower temperatures for smaller linewidths appear to indicate a size effect in the Stress Migration in advanced Cu interconnect scheme. The synchrotron x-ray micro-diffraction experiment, is used to show that plasticity is involved in the stress relaxation process at about 200° C, but not at higher temperature nor at room temperature. Such plasticity-assisted strain relaxation in interconnects especially at lower temperature range could explain the critical temperature shift observed in the present study, in addition to the typical diffusion-assisted mechanism. Further, the synchrotron X-ray micro-diffraction experiments also suggests indications of plasticity-assisted voiding. Numerical finite element analyses were also conducted in conjunction with the experimental study, to provide greater insight. The modelling result demonstrates the importance of creep plasticity in causing thermal stress relaxation in Cu interconnects.